2010
DOI: 10.1101/gr.106120.110
|View full text |Cite
|
Sign up to set email alerts
|

Function annotation of the rice transcriptome at single-nucleotide resolution by RNA-seq

Abstract: The functional complexity of the rice transcriptome is not yet fully elucidated, despite many studies having reported the use of DNA microarrays. Next-generation DNA sequencing technologies provide a powerful approach for mapping and quantifying the transcriptome, termed RNA sequencing (RNA-seq). In this study, we applied RNA-seq to globally sample transcripts of the cultivated rice Oryza sativa indica and japonica subspecies for resolving the whole-genome transcription profiles. We identified 15,708 novel tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
220
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(241 citation statements)
references
References 34 publications
16
220
2
3
Order By: Relevance
“…Retained intron, in which a single intron is alternatively included or spliced out of the mature mRNA via an intron-definition splicing mechanism, was the most prevalent type of AS event (30.4%; Fig. 3C), consistent with previous studies in plants (Black, 2003;Wang and Brendel, 2006;Barbazuk et al, 2008;Filichkin et al, 2010;Li et al, 2010;Lu et al, 2010;Zhang et al, 2010;Marquez et al, 2012) but in contrast to animal AS events, where exon skipping (cassette exons or coordinate cassette exons) is the predominant mechanism (Sultan et al, 2008;Wang et al, 2008;Daines et al, 2011;Graveley et al, 2011). Furthermore, alternative 39 splice sites (A3SS; 21.0%) or alternative last exons (ALE; 11.5%) and alternative 59 splice sites (A5SS; 12.2%) or alternative first exons (AFE; 11.7%) were other types of common AS events observed in our data (Fig.…”
Section: As Is Differentially Regulated Between Embryo and Endospermsupporting
confidence: 79%
See 3 more Smart Citations
“…Retained intron, in which a single intron is alternatively included or spliced out of the mature mRNA via an intron-definition splicing mechanism, was the most prevalent type of AS event (30.4%; Fig. 3C), consistent with previous studies in plants (Black, 2003;Wang and Brendel, 2006;Barbazuk et al, 2008;Filichkin et al, 2010;Li et al, 2010;Lu et al, 2010;Zhang et al, 2010;Marquez et al, 2012) but in contrast to animal AS events, where exon skipping (cassette exons or coordinate cassette exons) is the predominant mechanism (Sultan et al, 2008;Wang et al, 2008;Daines et al, 2011;Graveley et al, 2011). Furthermore, alternative 39 splice sites (A3SS; 21.0%) or alternative last exons (ALE; 11.5%) and alternative 59 splice sites (A5SS; 12.2%) or alternative first exons (AFE; 11.7%) were other types of common AS events observed in our data (Fig.…”
Section: As Is Differentially Regulated Between Embryo and Endospermsupporting
confidence: 79%
“…Previous studies have shown that NTRs have fewer and shorter exons, less protein-coding potential, and less tissue-specific expression than annotated protein-coding genes (Bruno et al, 2010;Lu et al, 2010;Wetterbom et al, 2010;Zhang et al, 2010;Aanes et al, 2011;Graveley et al, 2011). To determine whether endospermic and embryonic NTRs have similar features, we analyzed the structure, coding potentials, and expression levels of the NTRs.…”
Section: Discovery Of Ntrsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, recent reports have highlighted the abundance of novel transcriptionally active regions in rice that lack homology to proteincoding genes or open reading frames (ORFs) 40 . In barley as many as 27,009 preferentially single-exon low-confidence genes can be classified as putative novel transcriptionally active regions (Supplementary Note 7.1.4).…”
Section: Regulation Of Gene Expressionmentioning
confidence: 99%